Investigation of charge transport properties in VTP: PC71BM organic Schottky diode - Roslan, Nur Adilah; Supangat, Azzuliani; Sagadevan, Suresh (Multidisciplinary Digital Publishing Institute, 2022)
In this work, the charge transport properties of organic vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis(dimethylamino)-29H,31H phthalocyanine (VTP) were investigated. The I-V profile demonstrated by single VTP shows a rectifying behavior, and Schottky diode parameters such as the ideality factor, barrier height, shunt, and series resistance were calculated. Further, the charge transport behavior of single-layer VTP and its blend with phenyl C71 butyric acid methyl ester (PC71BM) was evaluated using the I-V conventional method and diode analysis. In addition, the optimized diode properties of VTP: PC71BM were chosen to evaluate its photovoltaic effect. The current density-voltage (J-V) characteristics were evaluated in both dark and light conditions to determine the key parameters of the photovoltaic effect. The results indicate the optimized VTP: the PC71BM composite blend yielded a relatively low photovoltaic efficiency. However, due to the presence of extended ligands, it gives a very good sensitivity when applied in the organic photodetector device, as reported in our previous work.